PENGARUH PERSEPSI PELANGGAN ATAS KUALITAS PELAYANAN DAN HARGA TERHADAP VOLUME PENJUALAN D’JOMBANG CAFÉ - M. Rizqi Sudirman (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research aims to determine the influence of customer perception of service quality and pricing on sales volume. The respondents of the research are the customers of D’Jombang Café, where the data are gathered through questionnaires. The samples are acquired utilizing random sampling. The multiple regression analysis of this research indicates that customer perception of service quality has positive and significant effect on sales volume, yet customer perception of pricing has no have effect on sales volume.Keywords: customer perception of service quality, customer perception of pricing, sales volume.